Methodologies for teaching Body and Movement Studies for teaching Arts/Dance (Revista NUPEART, 2023)
This article discusses some experiences made in two curri- cular components of the undergraduate dance course and the professional Master's in Arts Teaching at UFRN. The experiences explained are based on body and movement practices for teaching Dance and its possible applicability in basic education. The text relates these experiences with the contents of Dance Teaching and with what the BNCC preaches for teaching Art/ Dance.
Keywords: dance; bodily pratices; education